2017
DOI: 10.1021/acs.jafc.7b03614
|View full text |Cite
|
Sign up to set email alerts
|

The Mulberry (Morus alba L.) Fruit—A Review of Characteristic Components and Health Benefits

Abstract: Mulberry (Morus alba L.) fruit has a high yield in one fruiting season in many countries, especially in Asia, and a long history of use as an edible fruit and traditional medicine. A great diversity of nutritive compounds such as fatty acids, amino acids, vitamins, minerals, and bioactive compounds, including anthocyanins, rutin, quercetin, chlorogenic acid, and polysaccharides have been found in mulberry fruit depending on the cultivars and maturity stages. Furthermore, the extracts and active components of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
181
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(189 citation statements)
references
References 124 publications
6
181
1
1
Order By: Relevance
“…Mulberry ( Morus spp., family Moraceae), a fast‐growing deciduous tree, thrives under variable climate conditions ranging from temperate to tropical. China is the country with the largest area of mulberry, with greater than 626,000 hectares (ha) (Yuan & Zhao, ). The biomass yield of fresh mulberry leaves is approximately 25–30 tons/ha/year.…”
Section: Introductionmentioning
confidence: 99%
“…Mulberry ( Morus spp., family Moraceae), a fast‐growing deciduous tree, thrives under variable climate conditions ranging from temperate to tropical. China is the country with the largest area of mulberry, with greater than 626,000 hectares (ha) (Yuan & Zhao, ). The biomass yield of fresh mulberry leaves is approximately 25–30 tons/ha/year.…”
Section: Introductionmentioning
confidence: 99%
“…These results showed that G‐BS contained about 57% of polysaccharides and 1% of protein by dry mass. The polysaccharides content of G‐BS was much higher than that of ML‐BS (10%), TL‐BS (5%), TS‐BS (9%), and other plant such as: mushroom (5–10%) (Kalac, ) and different fruits (<21%) (Gao, Wu, & Wang, ; Yuan & Zhao, ).…”
Section: Discussionmentioning
confidence: 99%
“…(5-10%) (Kalac, 2009) and different fruits (<21%) (Gao, Wu, & Wang, 2013;Yuan & Zhao, 2017). and TS-BSP).…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants lessen the intracellular oxidative damage, through either direct or indirect cellular antioxidant activity. While phenolic compounds are capable of directly scavenging ROS via donation of hydrogen or electrons, cells are also protected by a network of endogenous antioxidant enzymes that protects against oxidative stress . Pretreatment with the phenolic extracts of lettuce significantly increased the activities of antioxidant enzymes (CAT and SOD) and their corresponding transcript levels in H 2 O 2 ‐treated Caco‐2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…While phenolic compounds are capable of directly scavenging ROS via donation of hydrogen or electrons, cells are also protected by a network of endogenous antioxidant enzymes that protects against oxidative stress. 2,3,36 Pretreatment with the phenolic extracts of lettuce significantly increased the activities of antioxidant enzymes (CAT and SOD) and their corresponding transcript levels in H 2 O 2 -treated Caco-2 cells. LP treatment was more effective than CP treatment with regard to protecting the antioxidant enzyme system under conditions of oxidative stress (Fig.…”
Section: Discussionmentioning
confidence: 99%